2023
DOI: 10.3390/coatings13081333
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modifications of Superparamagnetic Iron Oxide Nanoparticles with Polyvinyl Alcohol, Chitosan, and Graphene Oxide as Methylene Blue Adsorbents

Tran P. T. Quach,
Linh Doan

Abstract: Synthetic dye contamination of wastewater has long been a social issue, with adsorption being the most focused upon research technique among wastewater treatment. Using the co-precipitation method, superparamagnetic iron oxide nanoparticles (SPIONs) with the size of 13.6 ± 1.9 nm were synthesized. By adsorbing methylene blue (MB) on the modified surface of SPIONs using polyvinyl alcohol, chitosan, and graphene oxide, the entrapment efficiency at pH 7 can be up to 87.00 ± 0.16% after 13 days, and the highest MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(41 citation statements)
references
References 107 publications
5
36
0
Order By: Relevance
“…The adsorption isotherm can be calculated by applying the Langmuir isotherm (Equations ( 5)-( 8)) [27,28] the Freundlich isotherm (Equations ( 9) and ( 10)) [29], the Dubinin-Radushkevich (D-R) isotherm (Equation ( 10)) [28], the Temkin and Pyzhev isotherm (Equations ( 12)-( 14)) [30,31] and the Halsey isotherm (Equation ( 15)) model [32].…”
Section: %Lc =mentioning
confidence: 99%
“…The adsorption isotherm can be calculated by applying the Langmuir isotherm (Equations ( 5)-( 8)) [27,28] the Freundlich isotherm (Equations ( 9) and ( 10)) [29], the Dubinin-Radushkevich (D-R) isotherm (Equation ( 10)) [28], the Temkin and Pyzhev isotherm (Equations ( 12)-( 14)) [30,31] and the Halsey isotherm (Equation ( 15)) model [32].…”
Section: %Lc =mentioning
confidence: 99%
“…There are several approaches to treating dye effluents, including adsorption, ion exchange, flocculation, decantation, advanced oxidation processes, biodegradation, chemical precipitation, and other processes [6]. Among all of these techniques, adsorption has gained popularity for being an attractive option since, depending on the system, it is efficient, cost-effective, and simple to handle materials [7].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, several investigations have demonstrated that some undesired SPION aggregates may have lower stability, biocompatibility, and effectiveness. As a result, the use of SPION in conjunction with other stabilizing tools, such as carbon compounds, has been researched [6,10,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations